REVISITING MATHEMATICAL RESILIENCE AND ANXIETY AMONG SENIOR HIGH STUDENTS - Casinillo, Leomarich F; Casinillo, Emily L; Lagumbay, Christy T; Abad, Hannah Rissah F; Dagongdong, Myra L (Sanata Dharma University Yogyakarta, 2022)
Resilience is vital in recovering from mathematical anxiety since it gives motivation in pursuing despite obstacles and challenges. This study aimed to measure the mathematical resilience and anxiety of grade 11 students at Visayas State University-Main campus as well as to elucidate its relationship. Secondary data was used in this study from a current paper by Casinillo et al. (2020). Mean average, standard deviation, coefficient of variation, and Spearman rho correlation was employed to summarize and extract inference from the data. On average, the perception scores of students' levels of resilience and anxiety are 82.2 and 29.5, respectively. Results suggested that students are resilient and moderately anxious in learning mathematics. This implies that students are motivated even if they are facing some challenging problems in mathematics. On the other hand, students are somehow uneasy or experiencing a little worry in doing mathematical problems. Findings depicted that there is no significant relationship (p-value=0.4725) between the students' level of resilience and anxiety. This means to say that resiliency of students does not lessen the level of anxiety in learning mathematics. In that case, teachers must not only be focusing on the resiliency of their students but also on creativity, self-determination, and motivation, among others. Furthermore, to eliminate the anxiousness of students in facing mathematical problems, teachers must encourage and cultivate their interest in learning mathematics.